Menstrual status differences of elite Turkish female athletes from various team sports - Karacan, S.; Colakoglu, F. F.; Ersöz, G. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The aim of this study was to compare the menstrual state of professional Turkish female athletes who compete in different team sports. Methods: 133 female athletes (33 football, 29 basketball, 27 handball and 44 field hockey players) from different sports branches who take place in the Turkish Premier League and Turkish Super League by random sampling method participated to this study. The physical characteristics including age, weight and height of the subjects were detected and given in order as following; in handball 23.62±3.04 years and 60.74±5.13 kg, 168.92±6.74 cm in football, 22.21±3.33 years, 54.87±5.75 kg, 164.30±6.29 cm in field hockey 19.93±3.87 years, 52.31±6.25 kg, 164.95±5.56 cm and in basketball 22.72±2.85 years, 64.82±7.21 kg, 177.03±5.38 cm. As a data gathering tool, a questionnaire that was made up of 37 questions was applied to the participants, and the questions were asked face to face to each athletes. One-way ANOVA and Chi square tests were used for statistical analysis. Results: Although there was not found a significant relation between the menstrual status and the sports branches (Chi;2=3.893, p>.05), there was a significant relation between the sports branches and sports activities` changing the length of the menstrual period (Chi;2=12.165, p<.05). Among all the female athletes who pointed on their menstrual irregularity complaints out, the average was 8.3 %. There was not found significant relation between training frequency and menstrual cycle irregularity (Chi;2=1.178, p>.05). A significant relation was found between sports branches and the effects of menstruation on the sports activities on behalf of the female athletes who pointed out that they were psychologically affected by menstruation (Chi;2=15.53, p<.05). Discussion: As a result, menstrual irregularity was detected among Turkish Elite female athletes. This study showed that menstrual period would be significantly affected the performance in terms of psychological aspect. Therefore, this was explained that the length of the menstrual period might be affected the performance during sports activity.